An Overview of Microprocessor Control of Inverters - B. Rajender, Dr.; Sathyavani, B; Balakrishna, K.; R. Arulmurugan, Dr. (International Journal of Engineering and Technology, 2018)
Microprocessor technique empowers us to apply diverse control strategies in the present control systems, including control of electric drives. In the drive controller, the flag processors with inbuilt simple digital converters, clocks, beat width modulators and different gadgets, which streamline drive control, are regularly used.The different control methodologies are utilized to control the drives yet the improvement in semiconductor technology helped the utilization of power gadgets in the drives. The demand for reduced, solid and mechanized drives existed and the advancement of drive has occurred the correct way in assortment of utilizations like power supply, pulling forces, vehicles, and so forth which has no limits for the improvement. PC made the control techniques simple yet past that the microprocessor based single stage drives are demanded in the remote regions. Demand of control of power existed for a long time which drove early advancement of drives. Power handling capacities and exchanging speed of power drives has been expanded with improvement in semiconductor technology.The ongoing advancements in electrical drive technology are spurred by the expanding necessities of mechanical applications for higher execution, better unwavering quality, and lower cost. They are because of the advances in a few zones specifically power electronics, control theory, and microprocessor technology.Â Â